The Potential of Remote Sensing and GIS for Desertification Monitoring and Assessment - Hostert, P; Roder, A; Jarmer, T; Udelhoven, T; Hill, J (Annals of Arid Zone, 2016)
Remote sensing based data are a valuable source for extracting spatially and temporally explicit information to monitor and assess regions threatened by desertification processes. Additional value can often be added through integrating remote sensing derived information with auxiliary data through a geoinformatics approach. This paper first addresses the essential problem of implementing relevant conceptual frameworks, of identifying processes, and of developing process dependant indicators. Data processing has therefore to focus on prerequisites ensuring the optimum identification and quantification of such indicators. A number of case studies is presented to explicate the significance of quantitative indicator based concepts. Moreover, the importance of integrating socio-economic boundary conditions and anthropogenic influences is outlined. Finally, the perspectives of future developments and their likely implications for remote sensing and Geographical Information Systems (GIS) based desertification research are summarized.